Penerapan Pengecoran Logam Aluminium Menggunakan Cetakan Alternatif Campuran Silika dan Bentonite - Paschal Nicollas Dominggo Massa; Elisabet Priska Arkadewi Kononis; Randy Abednego Nathanael; Agustinus Iwanto; Lasman Parulian Purba; Lilis Nurhayati (Universitas Katolik Darma Cendika, 2024)
Metal casting is one of the manufacturing methods widely used to produce components with complex shapes and high precision. This study aims to evaluate the use of alternative molds based on a mixture of silica sand and bentonite in aluminum casting. Variations in the composition of silica sand and bentonite are applied in the casting process to observe their effects on the surface quality of the casting results and the efficiency of the production process. The results of field observations show that the optimal composition consists of 85% silica sand, 10% bentonite, and 5% graphite, which produces a mold mixture with good consistency, is not easily cracked, and is able to replicate pattern details with high precision. In addition, molds with this composition are easier to shape and have good resistance during the casting process, thereby reducing the risk of mold failure. Thus, molds based on silica sand and bentonite have the potential to be a more efficient and environmentally friendly alternative in metal casting technology.